Comparison of somatotype characteristics and anthropometric proportional relations of elite wrestlers between styles and weights - Öcal Kaplan, D.; Yildiran, I. (Journal of Education and Training Studies, 2018)
In this paper, comparison of somatotype characteristics and anthropometric proportional relations of elite wrestlers at the level of styles and weights and, contribution to improvement and orientation of sport is aimed. 57 elite wrestlers took place in the European Championship Preparatory Camp of Turkish National Adults Wrestling Team (31 Greco-Roman style with 7 light weight, 14 medium weight and 10 heavy weight -with av. height: 168.9 cm. and av. weight: 81.1 kg.; 26 free style with 8 light weight, 12 are medium weight and 6 heavy weight -with av. height: 173.0 cm. and av. weight: 87.9 kg), analysed in this study. As a result of anthropometric measurements, there are no meaningful differences between free style and Greco-Roman elite wrestlers both in style and weigh. Wrestlers, as evaluated in somatotype, free and Greco-Roman styles are characterized as endomorphic mesomorphy, lightweight wrestlers are measured as balanced mesomorphy, medium-weight wrestlers are found endomorphic mesomorphy and heavy-weight wrestlers are characterized as endomorphic mesomorphy. Meaningful difference have found between weights. In spite of there is no differentiate effect of styles for wrestlers, partake in the similar training, nutrition and competition programs from childhood, weight, leaning on differentiates of somatotypes in the frame of the components like height, weight, length of bust and arm etc., emanates differences.